Establishing the legal nature of unilateral acts of states - Konnova, Elena V. (Journal of the Belarusian State University. International Relations, 2018)
There is a well established proposition that an intent of a State to be bound is a primary criterion for establishing the legal character of a unilateral act. However, this proposition does not solve the problem of interpretation of a State’s intent to be legally bound and of determining whether a certain act is subject to unilateral acts of States regime. A range of unilaterally formulated statements and declarations are examined in the article with a view to reveal different aspects of the process of determination of legal nature of a particular act of a State. Based on results of consideration of negative security assurances, notifications on the adoption of legislative acts, promises of granting a visa-free regime, assurances to support the acceptance of a State in an international organization, suggestions are formulated concerning the evaluation of certain unilateral statements for qualifying them as legal acts.
Keywords: unilateral acts of States; unilateral promise; intent of a State